Aroma-producing yeasts associated with cocoa beans fermentation: starter culture selection for flavor modulation of chocolate - Alvarez, Jonatan Peregrino (2017)
Chocolate is one of the most important products for the food industry, being of economic interest all over the world. The cocoa quality depends directly on the post-harvest processing, being the cocoa-pulp fermentation a crucial step for chocolate quality development. The aim of this work was to study the diversity of aroma-producing yeasts associated with cocoa beans fermentation and to select suitable yeast starter culture to cocoa flavor modulation. A total of 39 cocoa-derived yeast isolates were screened for their capacity to produce volatile aroma compounds in a cocoa pulp simulation medium. The seven highest aroma-producing yeasts were identified by ITS-rRNA gene sequencing as belonging to Pichia kudriavzevii, in spite of exhibiting different metabolic profiles. A computer-assisted analysis of rep-PCR genomic fingerprints of Pichia kudriavzevii strains clearly differentiated the upper aroma-forming yeast strains (G1 group; P. kudriavzevii LPB06 and P. kudriavzevii LPB07) from the other strains (G2 group). This demonstrates the potential of rep-PCR technique as a promising genotypic tool for rapid and reliable speciation of aromatic yeast strains. In the second stage of this study, two strains with superior aroma production, namely P. kudriavzevii LPB06 and P. kudriavzevii LPB07, were used in cocoa beans fermentation at laboratory scale. They were able to establish an accelerated fermentation process with efficient yeast growth, sugars consumption and ethanol formation compared to the spontaneous process. The resulting cocoa beans were analyzed by diverse chemical analysis methods, including SPME-GC/MS, FTIR spectroscopy and metal and colorimetric analysis. All together, the results indicated that inoculated fermentations generated cocoa beans with better color development and richer aroma composition, suggesting that cocoa-associated yeast diversity at strain level can be exploited for flavor modulation of cocoa beans.